Application of Database Management Tools for On-line Dissemination of Information on Agroforestry in India Through World Wide Web - Kumar, Ajit; Rai, P.; Handa, A.K.; Choudhari, Sudhakar; Prasad, Y. V. Krishna; Pilli, Ajay Babu (Indian Journal of Agroforestry, 2020)
Agroforestry with its diversified and multifarious uses is gaining importance within the agricultural superset. However, information on packages, practices and system of agroforestry is not readily available to the end user, a farmer or extension worker. With the rapid development of Internet, it is now possible to put the information in electronic format so that users can access it any where and any time. The present investigation/ research activities are being carried out with the idea of developing a comprehensive online database on agroforestry entitled "agroforestryBASE" containing information on various aspects of agroforestry under four independent modules/ databases namely MPTS, research projects, economic analysis and agroforestry intervention/ innovations. The software runs on a HTTP server and serves the request of client on any computer connected with Internet and having a graphic web browser. There is provision to browse information through user-friendly interface. This article gives a brief account of Agroforestry Database Development Programme describing its concept, structure, sources of information, approaches, applications and limitations.